How and Where Did Students Learn Music in the Late Middle Ages and Renaissance? - Grantley McDonald (Muzyka)
Musicologists have traditionally focused on mature musicians working in musical centres such as courts and cathedrals. However, archives also contain much information about music in places that were geographically or administratively less central. Such places often render valuable information about musical education. The chapters in the book reviewed here present case-studies in musical education from the late Middle Ages until the early modern period. Many focus on the city and province of Padua, while others examine music education in German universities, Parisian parish schools, and French riding academies.